DETERMINANT FACTORS THAT AFFECT E- LEARNING APPROACH IN TEACHING AND LEARNING AT HIGHER EDUCATION: A LITERATURE REVIEW - Halimatus Sakdiyah Hosayni; Nur Fatin Syawani Suhaimi; Abdullah Muhamed Yusoff; Roslizawati Che Aziz; Nik Alif Amri Nik Hashim; Anis Nazihah Ahmad Nordin (Jurnal Penyelidikan Sains Sosial, 2020)
Recently, the eLearning market has growth up successfully as a result from the emerging of eLearning as the new paradigm of modern education. eLearning act as a medium consisting of various types of computer and electronic media which is communication tool as well as the Internet which provides training and certain subjects. By using eLearning, students can attend online classes anywhere, regardless of time and place. Generally, eLearning is more geared towards self-training and is ideal for individuals who work full-time but desire to further their studies. Thus, this study was developed and integrated the factors that lead to the effectiveness of eLearning approach in Teaching and Learning (T&L) system. The outcomes of this research will be helpful in developing new learning approach hence it is expected that the result of this study will reveal the effectiveness of eLearning based on few elements such as ICT skills, time management, resources and learning technique.